Interval-Valued q-Rung Orthopair Fuzzy QUALIFLEX Decision Analysis Method with Dombi Operators. (22nd February 2022) - Wan, Benting; Zhang, Xiaolu; Xiong, Meifang; Wang, Zhenwu
Abstract : As a new and useful decision tool, interval-valued q-rung orthopair fuzzy set (IVq-ROFS), has strong ability to address uncertain or imprecision information in practical decision-making processes. This paper develops a new interval-valued q-rung orthopair fuzzy QUALIFLEX decision analysis method with Dombi operators for handling the group decision-making problems with IVq-ROFSs data. We also conduct a case study on the health management of hypertensive patients for demonstrating the feasibility and superiority of the developed method. The main contributions of this paper are as follows: (1) we first propose interval-valued q-rung orthopair fuzzy Dombi operational laws and investigate their desirable properties; (2) using the developed Dombi operational laws, we develop an interval-valued q-rung orthopair fuzzy Dombi weighted average (IVq-ROFDWA) operator, and we prove that the IVq-ROFDWA operator satisfies the properties of idempotency, commutativity, boundedness, and monotonicity; (3) we introduce the concept of interval-valued q-rung orthopair fuzzy ideal group opinions with the help of IVq-ROFDWA operator and propose a new weight-determining method for identifying the weights of experts; (4) we develop a new interval-valued q-rung orthopair fuzzy distance measure. With the help of the developed distance measure, we calculate interval-valued q-rung orthopair fuzzy concordance/discordance index under each permutation, and then a new interval-valued q-rung orthopair fuzzy QUALIFLEX decision analysis method is developed for addressing the complex multiattribute group decision-making problems with IVq-ROFSs.